Pelatihan Peluang Usaha Sebagai Konten Kreator - Intan Pratiwi; Niwayan Ika Sari; Helmi Wachidatul Ulya; Shachadewi Maulida; Anugerah Dwi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
In this digital era, becoming a content creator is a promising business opportunity. This training aims to equip MSME players, KONI athletes and also the general public with the knowledge and skills needed to become successful content creators. Becoming a successful content creator is able to produce creative work that attracts the attention of the audience, build a strong personal brand and monetize their content in various ways. This training was delivered by one of the digital marketing online shops who provided practical strategies that they had implemented in their career journey. Participants will also have the opportunity to interact with presenters and fellow participants, build networks and exchange ideas, experiences.